A metal retainer manufactured by 3D printing. Issue 2 (28th September 2020) - Koizumi, So; Seimiya, Kazuhide; Park, Heetae; Nakashizu, Toshifumi; Suzuki, Kazuya; Otsuka, Takero; Kobayashi, Masaru; Hoshi, Noriyuki; Kimoto, Katsuhiko; Yamaguchi, Tetsutaro
ABSTRACT: Purpose: Retainers are crucial appliances for the long-term stabilityof occlusion after orthodontic treatment. However, patient discomfort or poor aesthetics often lead to a decline in compliance. Aiming to improve upon these qualities, this article illustrates anovel method for manufacturing a modified Hawley type retainer. Materials and methods: The proposed technique utilized a 3D printer. The acrylic plate was replaced by Co-Cr, and a clear and aesthetically pleasing organic polymer was used for the labial wire. Results: The modified Hawley retainer manufactured using the 3D metal printer could be fabricated with minimum thickness by using Co-Cr. In addition, the organic polymer wire enhanced theaesthetics. Conclusion: Our modified Hawley retainer has many advantages as a useful appliance that overcomes the drawbacks of conventional retainers. Although additional testing is required, patient comfortand ease of speaking after setting in the oral cavity are expected to be superior to those achieved with conventional retainers. The metal material has excellent durability and cleanliness, which brings great benefits to patients and orthodontists. Manufacturing with a 3D printer is expected to be an excellent alternative to conventional methods.